Experimental investigation of doubly-symmetric built-up I–girders subjected to high moment gradient. (15th May 2023) - Phillips, Matthew; Slein, Ryan; Sherman, Ryan J.; White, Donald W.
Highlights: The AISC 360 predicted flexural resistance was unconservative for the experiments. Full-nonlinear shell FEA solutions accurately predicted the measured strengths. The direct scaling by Cb overestimates the strength gains from moment gradient. The direct scaling by Cb does not sufficiently account for the onset of yielding. Web distortion and onset-of-yielding effects combine to cause strength reductions. Abstract: Recent analytical studies have shown that the AISC 360-16 Specification overpredicts the flexural resistance of certain built-up steel I-girders. The largest overpredictions were observed in I‑girders subjected to a high moment gradient having unstiffened webs with a large web slenderness ratio. The objectives of the current research are to provide experimental validation of these strength overpredictions, validate the accuracy of full-nonlinear shell finite element analysis (FEA) solutions, and further investigate the behavior of these susceptible built-up I-girders. To accomplish the objectives, six largescale experimental tests targeted web slenderness ratios ranging from 77 to 192 and a moment gradient factor, Cb, of 1.74 (single curvature (SC) bending) and 2.31 (reverse curvature (RC) bending), calculated using common design equations. Additionally, full nonlinear shell FEA simulations were conducted to evaluate the correlation with the experiments. The tests showed flexural strengths smaller than the predicted resistances from AISC 360, with the predicted resistances ranging from 4% to 16% unconservative for SC members and 9% to 32% unconservative for RC members. Furthermore, the FEA simulation strengths were similar to the strengths measured in the experiments. The results indicate that there are two main phenomena leading to the overpredictions by AISC 360: web distortion effects exacerbated by web shear and the direct scaling of the uniform LTB strength curve by Cb up to the plateau resistance, overestimating the strength gains from moment gradient due to insufficient accounting for the onset of yielding.